SISTEM INFORMASI TRACER STUDY ALUMNI PADA PRODI TEKNIK INFORMATIKA UNIVERSITAS MUHAMMADIYAH GRESIK BERBASIS WEB - Choyr Mukhlasin Candra Sakti; Soffiana Agustin; Harunur Rosyid (Universitas Muhammadiyah Gresik, 2019)
The name of the Higher Education Institution will be big, because of the alumni. However, the Informatics Engineering University of Muhammadiyah Gresik (UMG) continues to be required to always improve the quality of its educational process accompanied by efforts to increase its relevance in the context of global competition. Efforts to make improvements both in the academic and infrastructure fields have been carried out. The management of alumni data at Muhammadiyah Gresik University especially Information Engineering has not been overlooked and is still done manually. Alumni data is only stored in piles of paper in the administrative space, this can cause data damage and even data loss. The UMG Informatics Engineering tracer study activity provides an increase in education in teaching and learning activities so that it can improve the subsequent learning process. Therefore, to get information on the indications of lack of implementation of the study program the success of professionalism (career, status, and income) of alumni is needed. The Web-based Tracer Study Information System in Informatics Engineering Muhammadiyah Gresik University will be made easier for study programs to get information on relevant knowledge and expertise (the relationship between knowledge and expertise with work requirements, work scope, professional position) of the alumni. The value of the convenience obtained from the application questionnaire by users is 75.95% rounded up to 76%.